Springback Prediction and Compensation of Elastic-Perfectly Plastic Strip in Multi-Square Punch Forming (Advances in Applied Mathematics and Mechanics, 2020)
One-step forming study is a desired hull forming strategy in shipbuilding industry due to its high efficiency and economy. Compared with traditional mold forming, the multi-square punch forming (MSPF) can easily change its target shape by adjusting the height of its square punches. More importantly, MSPF provides uniformly distributed normal loading and a surface-to-surface contact between the punches and the plate, reducing plate wrinkles and dents to a great extent. This paper aims to provide solution to the one-step forming of elastic-perfectly plastic strip formed by MSPF machine. With deeper understanding of the mechanisms of the forming and the springback, accurate prediction of the springback is possible. By investigating the springback feature of the strip under MSPF, the curvature adjustment (CA) method is proposed to compensate the springback. The one-step MSPF model is then established on the basis of both the analytical model and the CA compensation method, which could properly decide the pre-designed die shape that produces the target shape of the strip. The present method is validated by published results and is proven to be in high accuracy. Case studies are also conducted by the present method to obtain the die shape of the flexible dies, which further validates the accuracy. Besides, the critical length is introduced for the particular cantilevered forming approach by the MSPF machine, and its effects on the forming accuracy and the formable range of the MSPF machine have also been discussed.